Issuance of Legally Defective Land Rights Certificates at the Jayapura City Land Office - Yoseph Palenewen, James (PT. Multidisciplinary Press Indonesia, 2025)
This study aims to determine the factors that cause certificates to be legally defective at the Jayapura City Land Office and to determine how to cancel certificates that are legally defective at the Jayapura City Land Office. The approach method used in this study is the normative and empirical legal approach method, namely an approach that refers to laws, literature, written regulations or other secondary legal materials and to see how it is applied through field research. The results of this study revealed that the factors that caused the certificate to be legally defective at the Jayapura City Land Office were 2 (two) main things, namely the first from the applicant himself with dishonesty by making fake documents from blank signatures to parties adjacent to the land, in other words it can be said that the applicant from the beginning had bad intentions with the intention of lying to the land office by entering false data, the second from the Land Office itself because of administrative legal defects such as procedural errors, errors in the application of laws and regulations, errors in the subject of rights, errors in the type of rights, errors in calculating the area, there is overlapping land rights, incorrect legal data or physical data or other errors of an administrative nature and the Way to Cancel a Certificate that is legally defective at the Jayapura City Land Office can be done by means of an application by the relevant party with a court decision that has permanent legal force.